Modernizing High School Agricultural Communications Competencies: A National Delphi Study - Mackenzie Atkins; Kati Lawson; Ricky Telg (Journal of Applied Communications, 2023)
The purpose of this study was to identify current competencies needed for high school students to succeed in their agricultural communication courses. This study also identified an ideal introduction level for each competency and provides up-to-date consensus on the most important agricultural communication competencies for high school students as determined by university faculty. Twenty years have passed since secondary agricultural communication competencies have been evaluated at a national level (Akers, 2000). Since then, industry standards have changed, including the emergence of social media, which is reflected in the results of this study. This study was conducted through a two-round Delphi study, in which the panel of experts consisted of agricultural communication university faculty from across the United States. The researchers found an additional 17 agricultural communication competencies needed in high school agricultural education. The findings in this study suggest that social media competencies should be added to high school agricultural communications curriculums. The results showed that 41 competencies (pre-identified and newly identified) did not reach the level of agreement necessary to be considered important in a high school agricultural communications curriculum. The researchers suggest that these findings should be used to create a standardized base curriculum for high school agricultural communication courses.
Keywords: Agricultural communication(s); high school; competencies; secondary agricultural education; agriculture education; competencies in education; Delphi